Influence of Various Binder Jet Printers on the Additive Manufacturing of Hardmetals - Christian Berger; Johannes Pötschke; Uwe Scheithauer; Alexander Michaelis (Crystals)
Binder Jetting (BJT), a powder-based additive manufacturing technology, has been shown to be a fast and reproducible green shaping process for many different metals. Due to its high productivity and versatility in material processing, BJT is gaining increasing importance in the manufacturing sector. It can also be used for the production of WC-Co hardmetals, a primary ceramic-based composite often used for tools and wear parts. Five different BJT printers from four different manufacturers were evaluated to assess their effectiveness and feasibility in producing hardmetals based on the same WC-12 wt.% Co starting powders. The analysis focused on comparing the properties of the resulting hardmetals, as well as evaluating the printing performance. The results show that all tested BJT printers are fundamentally well suited for producing green hardmetal parts, which can achieve full density after sintering. This work highlights the potential of BJT technology in hardmetal manufacturing for tool production.